Technology on Sleeping Patterns of Youths - Kushwaha, Ujjwal; Khadgi, Sushmita; Kafle, Sneha; Khadgi, Soniya (NPRC Journal of Multidisciplinary Research, 2024)
The increasing use of technology among youths has raised concerns about its impact on sleep patterns. This qualitative study explores how screen time affects sleep through in-depth interviews with young participants. Respondents shared that excessive use of technology, particularly before bedtime, made it harder to fall asleep and reduced the overall quality of their sleep. Engaging with social media, video games, or watching videos late at night heightened mental stimulation, making it difficult to relax and prepare for sleep. Additionally, prolonged screen time led to shorter sleep duration, leaving many feeling tired upon waking. These findings highlight the negative effects of excessive technology use on sleep, particularly when used close to bedtime. The study emphasizes the importance of creating strategies to reduce screen time before sleep, helping youths develop healthier sleep habits that are essential for their well-being and daily functioning. Promoting these habits is crucial for improving both mental and physical health.